Beverage Consumption in the Diets of Children is Not Consistently Associated with Weight: National Health and Nutrition Examination Survey 2007-2014 - Nicklas, Theresa A.; O’Neil, Carol E.; Fulgoni III, Victor L. (International Journal of Child Health and Nutrition, 2018)
Objectives: The objective of this study was to examine whether there was significant risk associated with types of beverages consumed on the weight status in children. Design: Nationally representative cross-sectional sample. Setting: Demographic information was obtained from the NHANES interviews. Dietary intake data were obtained from Day 1, in-person 24-hour dietary recall interviews administered using an automated multiple-pass method. Height and weight were obtained according to NHANES Anthropometry Procedures Manual. Subjects: Children 2-18 years of age. Results: The likelihood of being overweight or obese was not significant for any of the beverages studied between consumers and non-consumers. For the total sample, for every 29.6 mL of water consumed the risk of being obese was 1%. For ages 6-11 years water consumption increased the risk of being obese and in ages 2-5 years, consumption of sugar sweetened beverages (SSB) increased the risk of being obese. The risk of being obese was significant p <0.05 for Hispanic males for every 29.6 mL of water consumed and for 100% fruit juice and SSB for other males; increased risk was ?3%. The risk of being obese increased for White females for every 29.6 mL of flavored milk consumed and water consumption for both Black females and Hispanic females; the significant p<0.05 increased risk of obesity was ?7%. Conclusions: Beverage consumption was not consistently associated with weight status in the diets of a nationally representative sample of children. In some cases the increased risk was very small.